Pengaruh Organizational Culture dan Work Engagement terhadap Nurse Performance melalui Job Satisfaction sebagai variabel intervening - Raharjo, Nur Ramadhani; Husain, Muhammad (Universitas Negeri Surabaya, 2025)
This study aims to determine and explain the influence of organisational culture and work engagement on nurse performance through job satisfaction as an intermediary variable at XYZ Hospital. This is a quantitative study with a population of 87 nurses in the inpatient unit and a saturated sampling technique. The statistical analysis used in this study is Structural Equation Modelling (SEM) with the assistance of Smart Partial Least Square (PLS) 3.2.9 software. The results of this study indicate that work engagement and job satisfaction influence nurse performance, organisational culture does not influence nurse performance, organisational culture and work engagement influence job satisfaction, and job satisfaction mediates the influence of organisational culture and work engagement on nurse performance. The practical implications of this study suggest that hospital management needs to maintain consistency and enhance programmes that can improve work engagement and job satisfaction, such as providing recognition and rewards for performance, implementing regular mentoring programmes, involving nurses in decision-making, conducting periodic nurse satisfaction surveys, and creating an open and participatory work culture through improved vertical and horizontal communication.